Desafios em ensinar matemática nos anos iniciais - Tebas, Alyne de Moura Xavier (Universidade Federal do Tocantins, 2024)
This article aimed to understand the challenges of Mathematics Teaching in the Early Years of Elementary School from the literature in the area, articulated as memories of the formative path of a Pedagogy student. For the development of this work, studies were carried out on Mathematics Education, Teacher Education, articulated as memories of mathematics as a discipline experienced by the first research paper. The methodological construction was guided by the qualitative approach, and the data that constituted the investigation were collected through bibliographic and documentary studies, moved and records of the developed mathematics activities provided by the Study Group in Literacy and Numbering - GELEN / UFT, configuring itself as a case study. The field stage of this work was carried out in the municipality of Arraias / TO in a public school, in the 4th grade class of elementary school, during an activity guided by the GELEN group. Studying mathematics revelation for the early years is a challenge for teachers in providing relevant learning experiences for students. The gaps indicate in the aspects related to the initial and continuous training of teachers in the early years. It indicates the importance of academics participating in research groups at the university, as they contribute to understanding the challenges and propositions of solutions, breaking with the dissociation of theory and practice. It is a revelation that by reflecting their own memories, the learning processes enhance human development, contributing to the formation of obliged and professionally committed.